A criação do curso de engenharia química na escola nacional de química da universidade do Brasil - Silva,Alexandro Pereira da (2006)
The goal of this work was to establish the origins of the chemical engineering course at the National School of Chemistry of the University of Brazil (at present, the School of Chemistry of the Federal University of Rio de Janeiro). There was a previous Industrial Chemistry course at the Higher School of Agriculture and Veterinary, established in 1920, following the French model. This course was the basis of the creation of the National School of Chemistry in 1933. During the 1940s, teachers and students claimed for a new course in true connection with the needs of the country and to reach full valorization of their job. The structure of the new Chemical Engineering course was approved in 1946 and the first class begun in 1952. This course was of great importance during the Brazilian industrial development during the 1950s and 1960s.